2012
DOI: 10.1039/c2nr11594h
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth BaTiO3 nanocubes and their superlattice from an aqueous process

Abstract: Ordered aggregated BaTiO(3) nanocubes with a narrow size distribution were obtained in an aqueous process by using bis(ammonium lactate) titanium dihydroxide (TALH) as Ti source in the presence of oleic acid and tert-butylamine. Kinetics of the formation of BaTiO(3) nanocubes indicated that an in situ growth mechanism was dominant and the superlattice of nanocubes formed in situ through the growth of BaTiO(3) nanoparticles in Ti-based hydrous gel. The size and morphology of nanocubes were controlled by tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
127
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 28 publications
2
127
0
Order By: Relevance
“…By dynamic light scattering (DLS) measurements of ST and BT nanocubes in toluene, the average size of ST and BT nanocubes was determined to be 20 nm and BT nanocubes showed a narrow size distribution corresponding to be almost mono-dispersed in toluene. 14,15 On the other hand, ST nanocubes had rather wide band in the range of 50-70 nm in the DLS profile. 14 This result indicated that ST nanocubes were slightly aggregated in toluene.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By dynamic light scattering (DLS) measurements of ST and BT nanocubes in toluene, the average size of ST and BT nanocubes was determined to be 20 nm and BT nanocubes showed a narrow size distribution corresponding to be almost mono-dispersed in toluene. 14,15 On the other hand, ST nanocubes had rather wide band in the range of 50-70 nm in the DLS profile. 14 This result indicated that ST nanocubes were slightly aggregated in toluene.…”
mentioning
confidence: 99%
“…14,15 The microstructure of these dielectric nanocubes have been observed by a high resolution transmission electron microscope (HR-TEM). The high magnification profiles indicated that each had a cubic shape with sharp edges and clear lattice fringes without inner voids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A typical synthesis process was similar to the previous report 7),22), 23) and summarized in Fig. 1.…”
Section: Methodsmentioning
confidence: 86%
“…4)7) Especially, the authors have already synthesized BT NCs by hydrothermal method with aqueous compounds and organic surfactants. 7) Highly qualified BT NCs with 15 nm in a size were obtained by this method. Moreover, the authors also fabricated three-dimensional (3D) BT NC packing structures by using capillary-force-assisted selfassembly method.…”
Section: Introductionmentioning
confidence: 99%